Assessment of Changes in Water Resources of the Upper Aras Transboundary Basin Under the Influence of Increasing Cultivated Area, Using the SWAT Model and Global Climate Databases - Mohammadreza Hajihoseini; Saeed Morid; Samad Emamgholizade; Emad Mahjoobi; Bahram Amirahmadian; Houshang Gholami (تحقیقات منابع آب ایران)
The Upper Aras transboundary Basin, shared between Turkey and Armenia, has undergone significant agricultural development...